Fluctuations in willingness to communicate of an EFL lecturer: An observation study in Indonesia - Marhamah Ika Putri (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2021)
Despite the growing number of research on Willingness to Communicate (WTC) in English students, research of teachers’ WTC in English is still scarce. At the same time, the fluctuations of WTC in English in authentic classroom interactions are still under research. This study aims to observe the fluctuations in WTC of the English lecturer in the Indonesian context. The data were collected through video recordings during an online classroom learning session where participants were teaching their students. The data were then transcribed, coded, and analyzed thematically by drawing from MacIntyre et al.’s (1998) Heuristic Model. From the results of the analysis, WTC fluctuations in English are divided into four factors: (1) modeling the use of English in the classroom, (2) the power of affirmation, (3) focusing on the message, and (4) showing language similarity. The implication of this study is also discussed.  DOI: 10.26905/enjourme.v6i2.5983